Topical ciclosporin in the treatment of vernal keratoconjunctivitis in Rwanda, Central Africa: a prospective, randomised, double-masked, controlled clinical trial. Issue 3 (14th October 2011) - De Smedt, Stefan; Nkurikiye, John; Fonteyne, Yannick; Tuft, Stephen; De Bacquer, Dirk; Gilbert, Clare; Kestelyn, Philippe
Abstract : Aim: To compare the short-term efficiency and safety of topical ciclosporin A (CsA) 2% with dexamethasone 0.1% in the treatment of predominantly limbal vernal keratoconjunctivitis (VKC) in Rwanda, Central Africa. Methods: Consecutive patients with VKC were randomised in a prospective, double-masked, clinical trial to receive either topical CsA 2% dissolved in olive oil vehicle or dexamethasone 0.1% drops for 4 weeks. Both groups then received sodium chromoglycate 2% drops for maintenance therapy for a further 4 weeks. The primary outcome was the reduction in composite score for VKC-related symptoms and signs at 4 weeks. Secondary outcomes included side effects, best-corrected visual acuity, comfort rating of the trial drops during 4 weeks' test medication and relapse rate thereafter. Results: The 366 participants recruited had the limbal (91.5%) or mixed form of VKC. At the end of the 4-week treatment period, the composite score had decreased significantly (p<0.001) from baseline without any significant difference between CsA and dexamethasone (p=0.20). There were no severe adverse reactions, but CsA drops caused more stinging than the oil placebo and dexamethasone (p<0.001). In both treatment groups, the visual acuity had improved at 4 weeks compared with baseline (p<0.001) with no significant difference between the treatment arms. The relapse rate following cessation of the trial treatments was similar (p=0.84) in both groups. Conclusion: There is no significant difference between the efficiency of topical CsA 2% and dexamethasone 0.1% for the management of acute VKC in Central Africa, but tolerance needs to be improved.